Metabolomic changes in Cryptocaryon irritans from Larimichthys crocea after exposure to copper plate - Guo, Xiangyu; Huang, Wenlian; Xu, Yifan; Zhan, Quanjun; Sun, Peng; Hu, Haojie (Frontiers in Cellular and Infection Microbiology, 2024)
Cryptocaryon irritans is a highly detrimental parasite in mariculture, causing significant economic losses to the aquaculture industry of Larimichthys crocea. In recent years, copper and copper alloy materials have been used to kill parasites. In this study, the effect of copper plates on the tomont period of C. irritans was explored. The findings indicated that copper plates effectively eradicated tomonts, resulting in a hatching rate of 0. The metabolomic analysis revealed that a total of 2,663 differentially expressed metabolites (1,032 up-regulated and 1,631 down-regulated) were screened in the positive ion mode, and 2,199 differentially expressed metabolites (840 up-regulated and 1,359 down-regulated) were screened in the negative ion mode. L-arginine and L-aspartic acid could be used as potential biomarkers. Copper plate treatment affected 25 metabolic pathways in the tomont, most notably influencing histidine metabolism, retinol metabolism, the biosynthesis of phenylalanine, tyrosine, and tryptophan, as well as arginine and proline metabolism. It was shown that high concentrations of copper ions caused a certain degree of disruption to the metabolome of tomonts in C. irritans, thereby impacting their metabolic processes. Consequently, this disturbance ultimately leads to the rapid demise of tomonts upon exposure to copper plates. The metabolomic changes observed in this study elucidate the lethal impact of copper on C. irritans tomonts, providing valuable reference data for the prevention and control of C. irritans in aquaculture.